PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN IPA BIOLOGI SMP KELAS VII TAHUN PELAJARAN 2013/2014 - Myrna Amelia Ryani; Evi Suryawati; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to development of interactive multimedia in natural science subject junior high school grade VII SMP 2013/2014. Interactive Multimedia developed using Macromedia Flash 8 software. The research was conducted in Biology Education Program FKIP University of Riau in January-June 2014. The research uses Research and Development (R & D) approaches ADDIE model and carried out until implementation phase. The subjects were Core Competence and Basic Competence of junior high school grade VII. Data collecting instruments used validation sheet and questionnaire. Data were collected by filling validation sheet by validator validator distinguished into internal and external validators. Questionnaires filled out by members of the biology teacher MGMP Pekanbaru City totaling 20 people. Validation sheet and a questionnaire filled out for each aspects: design, pedagogical aspects, aspects of the content, and programming aspects. The collected data was analyzed by descriptive statistics. The results validate the development of multimedia interactive learning is 4.43 to 4.59 (very valid). Acquisition average scores on each of these aspects, namely: designing aspect has an average score of 4.43 (very valid), pedagogic aspect has an average score of 4.55 (very valid), the content aspect has an average score of 4.59 (very valid) , aspects of programming has an average score of 4.50 (very valid). The results of the analysis of teachers' responses to the questionnaire interactive learning multimedia that has been developed gained an average of 4.67 (Good) Based on this, it can be conclution that the development of interactive multimedia in natural science subject junior high school grade VII SMP 2013/2014can be used and implemented with very valid validity criterion.Key words: research & development, interactive multimedia, natural science subject junior high school